Vascular pedicle division during free flap re‐inset in pharyngoesophageal reconstruction. Issue 2 (14th May 2019) - Yegin, Mehmet Emre; Chen, Shih‐Heng; Chen, Hung‐Chi
Abstract: Background: Free intestinal flaps for pharyngolaryngoesophagus reconstruction may require revision operations, including free flap re‐inset for functional improvement. This report aimed to present our experience on vascular pedicle division at the secondary procedure of free flap re‐inset for functional improvement in pharyngoesophageal reconstruction. Patients and Methods: Eight male and seven female patients, with a mean age of 52 years old (range: 28–78 years), underwent pharyngoesophageal stricture (n = 7) and hypopharynx carcinoma reconstruction (n = 8) with three free jejunal and 12 free ileocolonic flaps. During revision procedure to shorten the flap for functional improvement, which was performed at 3 months after the initial operation, there were 11 venous and 4 arterial pedicle division cases. The intestinal flap circulation signs, such as presence of normoperistalsis, pink color, moderate secretion, and bleeding at puncture site, were observed for 1 hr. Results: No venous pedicle divisions required reanastomosis. However, all arterial pedicle division cases required immediate restoration with a vein graft because of immediate intestinal changes. No postoperative complications were seen, excluding a patient with anterior wall reconstruction who had arterial division and reanastomosis. Patients were followed up for a median duration of 28 months. Conclusion: For revision operations involving free intestinal flaps, the arterial pedicle must be protected or repaired if transected, whereas the venous pedicle does not necessitate such a maneuver.